PENGARUH DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, DAN DANA BAGI HASIL TERHADAP INDEKS PEMBANGUNAN MANUSIA DENGAN BELANJA MODAL SEBAGAI VARIABEL INTERVENING (STUDI EMPIRIS PADA PEMERINTAH DAERAH KABUPATEN/KOTA PROVINSI JAWA TENGAH TAHUN 2017-2020) - Sinta Nur Azizah (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study has a purpose, namely to determine the effect of the General Allocation Fund, Special Allocation Fund, and Profit Sharing Fund on the Human Development Index with Capital Expenditure as an Intervening Variable. The population in this study is DAU, DAK, DBH, Capital Expenditure, and HDI in the Regency/City of Central Java Province in 2017-2020. The samples used in this study were 124 samples. The method of sample collection using purposive sampling technique. The statistical method uses multiple linear regression analysis model. The results of this study indicate that DAK has an effect on HDI, while DAU and DBH have no effect on HDI. Furthermore, DAU has an effect on HDI through Capital Expenditures, while DAK and DBH have no effect on HDI through Capital Expenditures.